THE ROLE OF SOCIAL INVESTING EFFICACY IN MEDIATING THE EFFECT OF INDIVIDUAL VALUES ON ETHICAL INVESTMENT DECISIONS - Hanifa, Khoiro Uma; Atmini, Sari (UI Scholars Hub, 2023)
Along with the development of global issues regarding climate change, inequality, and pandemics, ethical investors now can integrate environmental and social aspects through sustainable- and responsible-based investment decisions which allow them to not only focus on financial goals. This study aims to investigate whether individual values, i.e., religiosity, altruism, and egoism, directly influence sustainable- and responsible-based investment decisions. This study also aims to find empirical evidence that those individual values (religiosity, altruism, and egoism) indirectly influence sustainable- and responsible-based investment decisions through social investing efficacy (SIE). The respondents of this study are 96 short-term Indonesian individual investors. Using structural equation modeling, this study does not succeed in finding evidence that religiosity, altruism, and egoism have direct influences on sustainable- and responsible-based investment decisions. However, this study documents that religiosity, altruism, and egoism indirectly influence sustainable- and responsible-based investment decisions through social investing efficacy.